The restorative potential of senior centers. Issue 4 (8th July 2014) - S. Rosenbaum, Mark; C. Sweeney, Jillian; Massiah, Carolyn
Abstract : Purpose: – The purpose of this paper is to help senior center managers and service researchers understand why some patrons experience health benefits, primarily fatigue relief, through senior center day services participation. Design/methodology/approach: – The authors conduct two separate studies at a senior center. The first study represents a grounded theory that offers an original, basic social process regarding mental restoration in senior centers. The second study draws on Attention Restoration Theory (ART) and employs survey methodology. Findings: – Senior center patrons who perceive a center's restorative stimuli experience health benefits such as relief from four types of fatigue, enhanced quality of life, and improved physical and mental well-being. Research limitations/implications: – The paper shows that senior centers may be relatively inexpensive, non-medical services that can help patrons relieve fatigue symptoms, which are often treated with pharmaceutical medication and medical visits. A limitation is the small sample size, which restricts generalizability. Practical implications: – The results show that senior center managers may promote patron health by fostering service designs and programs that allow members to temporarily escape from everyday life and interact in an ever-changing environment that fosters a sense of belonging. Social implications: – Senior center day services help patrons relieve fatigue, and its symptoms, in an affordable, non-medical, and non-pharmaceutical manner. Originality/value: – The paper clarifies the role of senior centers in patrons' lives by drawing on ART. Senior centers that can offer patrons restorative environments are likely to play a significant role in patrons' physical, social, and mental well-being.